Examining the Pattern of Corpus Representation in President Prabowo Subianto's Speech Using Antconc - Simanjuntak, Faido Marudut Pardamean (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2025)
This study examines the representation patterns found in Prabowo Subianto's corpus of presidential speeches. This is qualitative research using the results of the AntConc application. The method in this research is descriptive statistics. The data in this study was sourced from the transcript of President Prabowo Subianto's speech in 2024. This data is saved in a text file. txt format using UTF-8 encoding to facilitate processing with a corpus analysis tool. AntConc is the instrument utilized in this research. It draws attention to frequently occurring terms and keywords in the corpus and examines text structures with specific letter configurations. Additionally, from the frequency and keyword analysis of the 2024 speech text, it is found that the most commonly used word in Prabowo Subianto's speech text in 2024 is kita (we). This becomes evident that Prabowo Subianto is acting as the speaker, aiming to bring together himself and others, specifically all Indonesian citizens, in a united effort to reach the goal and directing his focus toward accomplishing the objectives for the Indonesian nation and state.